ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DAN BRAND IMAGE SERTA DAMPAKNYA TERHADAP MINAT BELI ULANG MASKAPAI LION AIR (Studi pada konsumen maskapai lion air di Kota Semarang) - Komala, Arine Magna; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2018)
The problem that happened to Lion Air at this time is the decrease of its market share consistently indicating the decrease of consumer interest using Lion Air service. Based on existing data is known that there is dissatisfaction and decrease customer image brand. This study aims to analyze the effect of service quality, price perceptions and promotion of customer satisfaction and brand image and its impact on consumer interest in using Lion Air services.The population used in this study is all Lion Air consumers in Semarang. The sampling technique used is accidental sampling. Sample criteria taken is a minimum of 172 people Lion Air consumers in Semarang. Methods of data collection in this study using questionnaires. Method of data analysis using structural equation modeling.Based on the results of service quality, price and promotion perceptions have a positive effect on customer satisfaction and brand image and have a positive impact on consumer interest in using Lion Air.